2021
DOI: 10.3389/fimmu.2021.764937
|View full text |Cite
|
Sign up to set email alerts
|

Primary Peripheral Epstein-Barr Virus Infection Can Lead to CNS Infection and Neuroinflammation in a Rabbit Model: Implications for Multiple Sclerosis Pathogenesis

Abstract: Epstein-Barr virus (EBV) is a common herpesvirus associated with malignant and non-malignant conditions. An accumulating body of evidence supports a role for EBV in the pathogenesis of multiple sclerosis (MS), a demyelinating disease of the CNS. However, little is known about the details of the link between EBV and MS. One obstacle which has hindered research in this area has been the lack of a suitable animal model recapitulating natural infection in humans. We have recently shown that healthy rabbits are sus… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 79 publications
0
4
0
Order By: Relevance
“…These animals displayed focal CNS cellular aggregates composed of densely clustered blood-derived macrophages surrounded by activated microglia and astrocytes, neutrophils, CD8 + T lymphocytes, dispersed EBI2 + cells and PCNA + , IgM + , and IgG + B lymphocytes ( Figure 1 ). Remarkably, the cell aggregates showed myelin damage in the center ( Figure 1 ) ( 56 ). This may model the early stages of lesions that progress into MS smoldering active plaques ( 78 ).…”
Section: Rabbit Model Of Ebv Infectionmentioning
confidence: 99%
See 3 more Smart Citations
“…These animals displayed focal CNS cellular aggregates composed of densely clustered blood-derived macrophages surrounded by activated microglia and astrocytes, neutrophils, CD8 + T lymphocytes, dispersed EBI2 + cells and PCNA + , IgM + , and IgG + B lymphocytes ( Figure 1 ). Remarkably, the cell aggregates showed myelin damage in the center ( Figure 1 ) ( 56 ). This may model the early stages of lesions that progress into MS smoldering active plaques ( 78 ).…”
Section: Rabbit Model Of Ebv Infectionmentioning
confidence: 99%
“…A recent study examined if EBV, following primary infection, could enter the rabbit CNS and by what mechanism ( 56 ). The study revealed that, at day 14 of infection, the levels of viral DNA were highest in both peripheral and CNS compartments.…”
Section: Rabbit Model Of Ebv Infectionmentioning
confidence: 99%
See 2 more Smart Citations